147. Setup accuracy in Lung Stereotactic Body Radiation Therapy (SBRT): Single lesion versus multiple lesions. (December 2018) - Vaccara, E.M.L.; Gho, A.; Belgioia, L.; Vagge, S.; Marcenaro, M.; Corvò, R.; Levrero, F.
Abstract : Purpose: To analyse setup accuracy for patients we use Octavius® (PTW Freiburg) 4D checks and post-treatment off-line images provided by Varian Aria (v.13.5). We focused attention on lung SBRT treatments with 6XFFF MV arcs delivered by Trilogy LINAC (Varian). An interesting case for quality assurance and SWOT (Strengths/Weaknesses/Opportunities/Threats) analysis is represented by multiple or bilateral diseases, that need more than one isocenter. The Aria system gives instructions to linac to manage plans with two isocenters as if dose distributions are disjointed. We would therefore like to avoid a dose increase between multiple isocenters (Threat). Methods: Image Guided RT (IGRT) is particularly useful when high tumoricidal doses are prescribed with highly conformal treatment modalities, including SBRT[1] . We retrospectively evaluated 55 consecutive patients that underwent Cone Beam Computed Tomography (CBCT) before each SBRT session and receive high dose in few fractions. Pre-treatment checks are evaluated with γ (3%;3 mm)-index. Forced compression method using a plate to compress abdomen is used in the 96% of treatments, in others a thermoplastic orfit is customized. We collect vertical, lateral and longitudinal shifts of the isocenter to calculate the 3D vector, defined as E = vert 2 + long 2 + lat 2 session by session[2] . Results: γ (3%;3 mm) is always 93%, instead the median E vector is 0, 71 cm for a total of 44 treatments with single-isocenter and 0, 36 cm for 27 multi-isocenter plans. An assessment of the dose changes of the recalculated plans on calibrated CBCT is underway preliminary results are shown in the table. Displayed dynamic range is optimal for all the ultrasound scanners (coefficient of determination R2 ⩾ 95%) and the maximum value is ABUS and Samsung score of 99%. Distance measures are coherent, there is no geometric distortion. The analysis of the Point Spread Function is underway with advanced mathematical methods. Conclusions: Even if the dose from CBCT for patients with multi-isocenter plans increases proportionally to the number of isocenters, we can say that the quality of positioning seems to have really improved.